Comparative study of vaginal Lactobacillus phages isolated from women in the United States and Turkey: Prevalence, morphology, host range, and DNA homology - Kiliç, AO; Pavlova, SI; Alpay, S; Kiliç, SS; Tao, L (Amer Soc Microbiology, 2001)
Lactobacilli play an important role in maintaining vaginal health. However, during bacterial vaginosis lactobacilli decrease for unknown reasons. Our preliminary study showed that phages could infect vaginal lactobacilli, Therefore, the aim of this study was to analyze the distribution, virulence, and types of vaginal Lactobacillus phages isolated from women of two countries: the United States and Turkey. A total of 209 vaginal lactobacilli were isolated from reproductive-aged women in the United States (n = 107) and Turkey (n = 102), By analysis of 16S rRNA gene sequence and by comparison of protein profiles, most lactobacilli were identified as L. crispatus, L. gasseri, and L. jensenii, After mitomycin C induction, 28% of American lactobacilli and 36% of Turkish lactobacilli released phages, A total of 67 phages were isolated and further characterized by their host range, electron microscopy, and DNA homology, All 67 phages were infective against iactobacilli from both collections. The host ranges of most phages were broad, including multiple Lactobacillus species. Even though the phages were all temperate, they were able to cause lytic infection in various strains. The electron micrographs of these phages showed a hexagon-shaped head and a long tail with or without a contractile tail sheath. Based on their morphology, these phages belonged to Bradley's phage groups A and B, and could be further classified into four morphotypes. All four types were found among American phages, but only three were found among Turkish isolates. DNA hybridization with labeled probes of the four types of phages revealed that additional genetic types existed within each morphotype among these phages. The phage genomic sizes ranged between 34 and 55 kb. Many of the lysogenic Lactobacillus strains released phages spontaneously at a high frequency of 10(-3) to 10(-4) PFU/cell, In conclusion, lysogeny in vaginal lactobacilli is widely spread. Some lysogenic lactobacilli spontaneously release phages with a broad host range, which can be Lytic against other vaginal lactobacilli regardless of their geographic origin.
Keywords: Bacterial Vaginosis; Preterm Delivery; Microbial-Flora; Genital-Tract; Bacteriophage; Infection; Identification; Birth